Потокові моделі мережі Інтернет за умов атак на відмову - Andon, Ph.I.; Ignatenko, O.P. (Інститут програмних систем НАН України, 2015)
This paper deals with fluid controlled models of networks under flooding denial of service attacks. We proposed a new approach to analyzing network work using fluid models and conflict control theory domain. Using analytic model there is found solution for certain class of networks and Nash equilibrium. We consider special case of network activity – denial of service attack and found dependency on download time depending of attack direction and traffic volume. The theoretical results were tested in simulation environment NS-2.